ARANG AKTIF KAYU WARU (Hisbiscus tiliaceus) SEBAGAI BAHAN PENGISI KOMPON SOL LUAR SEPATU CASUAL - Himawan Hendro Santopo (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2016)
The objective of this research was to obtain a weight (per hundred rubber) of hibiscus wood active carbon as a filler and vulcanization time in the outsole compound production of casual shoes. Variations in weight of hibiscus wood active carbon are 25 phr, 30 phr, 35 phr; and those in vulcanization time are 10 minutes and 15 minutes. Phr of hibiscus wood active carbon as a filler and vulcanization time significantly affects the physical properties of outsole compound on tensile strength, tear resistance, abrassion resistance, and bend-cracking resistance. The best formula is the P3W2 (the weight of hibiscus wood active carbon is 35 phr and the vulcanization time is 15 minutes), equal to the raw formula of outsole compound and complies the SNI 0778:2009 with the physical properties of outsole compounds on tensile strength 82,76 kg/cm2, tear resistance 48,75 kg/cm2, abrassion resistance 201,59 DIN/mm3 , and bend-cracking resistance which is not crack for 150.000 times deflection.